Peran Pendidikan Islam dalam Membentuk Kecerdasan Emosional Peserta Didik - Fadhillah Quratul ‘Aini; Rahmi Yuli Andini Hasibuan; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic education plays a vital role not only in cognitive development but also in nurturing students’ moral and spiritual values, which significantly contribute to emotional intelligence. This study explores how Islamic education aids in developing students' abilities to recognize, manage, and express emotions in positive and constructive ways. Core Islamic principles such as patience (ṣabr), trust in God (tawakkul), and maintaining good relationships (silaturrahim) are emphasized as essential components in shaping emotional resilience and empathy. By integrating these values into the curriculum, Islamic education fosters a supportive and value-based learning environment that encourages holistic development. The study highlights that emotional intelligence in Islamic education is not treated as a separate discipline but as an integral part of character formation and spiritual growth. Through classroom practices, religious teachings, and interpersonal interactions, students are guided to internalize emotional maturity aligned with ethical and spiritual ideals. As a result, Islamic education contributes to the balanced development of intellect, emotion, and morality, equipping students with the emotional and social skills necessary for personal well-being and community life.